Patient-led Goal Setting: A Pilot Study Investigating a Promising Approach for the Management of Chronic Low Back Pain. Issue 18 (15th September 2016) - Gardner, Tania; Refshauge, Kathryn; McAuley, James; Goodall, Stephen; Hübscher, Markus; Smith, Lorraine
Abstract : Study Design: A prospective, single-arm, pre-postintervention study. Objective: The aim of this study was to test the preliminary effectiveness of a patient-led goal-setting intervention on improving disability and pain in chronic low back pain. Summary of Background Data: An effective intervention for the treatment of chronic low back pain remains elusive despite extensive research into the area. An intervention using patient-centered goal setting to drive intervention strategies and encourage self-management for patients suffering chronic low back was developed. Methods: A single group longitudinal cohort pilot study was conducted. Twenty participants (male = nine) experiencing chronic low back pain were involved in a patient-led goal-setting intervention, facilitated by a physiotherapist over a 2-month period with two monthly follow-up sessions after treatment conclusion. Participants, guided by the therapist, identified problem areas of personal importance, defined goals, and developed evidence-based strategies to achieve the goals. Participants implemented the strategies independently between sessions. Primary outcome measures of disability and pain intensity were measured at baseline, 2, and 4 months. Secondary measures of quality of life, stress and anxiety, self-efficacy, and fear of movement were also taken. Results: Significant improvements (repeated analysis of variance P < 0.05) were seen in measures of disability, pain, fear avoidance, quality of life, and self-efficacy over the period of intervention and were maintained for a further 2 months after treatment conclusion. Conclusion: This intervention is novel because the goals set are based on patients' personal preferences, and not on treatment guidelines. Our findings confirm that a patient-centered goal-setting intervention is a potentially effective intervention for the management of chronic low back pain showing significant improvements in both quality of life and pain intensity. Level of Evidence: 4